Leaves at low versus high rainfall coordination of structure, lifespan and physiology - Wright, Ian J (The New phytologist, 2002)
•  Across species, leaf lifespan (LL) tends to be correlated with leaf mass per area (LMA). Previously we found that Australian perennial species from low-rainfall sites had c . 40% shorter LL at a given LMA than high-rainfall species. •  Here we relate indices of leaf strength (work to shear, W shear , and tissue toughness) to LL and LMA across the same suite of species. W shear is the work required to cut a leaf with a blade; W shear divided by leaf thickness gives tissue toughness. •  Low- and high-rainfall species did not differ in their LL at a given W shear , but dry-site species had lower W shear at a given LMA, leading to the observed LL - LMA shift with rainfall. These patterns were driven by 50% lower tissue toughness in dry-site species. •  The lower toughness was linked with high leaf N concentration, which is known to enhance water conservation during photosynthesis in low-rainfall species. Our results suggest that a significant cost of this strategy is reduced LL for a given investment in leaf tissue (LMA)